2021
DOI: 10.48084/etasr.4092
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Wear Resistant Iron-Steel: A Theoretical and Experimental Research on Wear Behavior

Abstract: In this study, four different alloys of steel blocks with a thickness of 15mm were manufactured in order to develop an alternative to steel plates used in wear exposed areas of construction machines, trucks, and asphalt production plants. To further increase the wear resistance of the manufactured steel blocks, their thickness was reduced to 10mm by the hot-rolling method. Wear specimens were obtained from rolled blocks. These specimens were abraded at 20N, 40N, and 60N loads in reciprocating linear motion mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…or complex tools (carbon fiber draping mold for the manufacture of aircraft doors, etc.) increasing demands, such as safety, reliability, performance, weight reduction, sustainable process, cannot be met by traditional materials, especially when the system is submitted to high mechanical, thermal, and chemical solicitation [1][2][3][4]. Aluminum alloys can be a suitable alternative to the materials supporting different types of in-service load [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…or complex tools (carbon fiber draping mold for the manufacture of aircraft doors, etc.) increasing demands, such as safety, reliability, performance, weight reduction, sustainable process, cannot be met by traditional materials, especially when the system is submitted to high mechanical, thermal, and chemical solicitation [1][2][3][4]. Aluminum alloys can be a suitable alternative to the materials supporting different types of in-service load [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As far as different kinds of bearings, sealing valves, etc., are concerned, common failure modes are also related to wear, which significantly decreases the serviceability limit and the effective utilization of these components [1][2][3]. Previous studies have suggested that most wear failures of valves and bearings, usually originating or initiating on their surface and gradually propagating to the interior, are sensitive to surface performance and microstructure [4,5]. Generally, excellent surface wear resistance can effectively improve the surface durability of substrate materials in a desirable way and be obtained by means of coating and deposition technologies, such as physical and chemical vapor deposition [6], electro-deposition [7], laser cladding [8], thermal spraying [9], surfacing [10], and so on.…”
Section: Introductionmentioning
confidence: 99%